Study on heat exchange of groundwater under complex geological conditions in karst area of south China - Wang, Kun; Wang, Wanjiang; Huang, Lidong (Frontiers in Earth Science, 2023)
This paper takes a groundwater source heat pump in the region as the research object and based on field research, experimental tests combined with comparative analysis, the data on its operation is monitored and analyzed in terms of operation, energy saving, and environment. The results show that the cooling temperatures of the test rooms were all below 26°C, the average coefficient of performance of the units was 4.61–4.93 and the average coefficient of performance of the system was 3.08–3.27. In addition, compared to conventional water-cooled chillers, 466 tons of standard coal could be saved in one cooling season, resulting in a reduction of 1,150.8 tons of carbon dioxide emissions, 9.3 tons of sulfur dioxide emissions and 4.7 tons of dust emissions The savings in operating costs are 793,000 RMB. This shows that the groundwater source heat pump has good energy efficiency and economy. The research results obtained in this paper provide a reference for improving energy efficiency and optimizing the operation of the groundwater source heat pump system. It is of great significance to the application of groundwater source heat pump systems in areas with complex geological environments.